2015
DOI: 10.1111/ggi.12518
|View full text |Cite
|
Sign up to set email alerts
|

Depression in left‐behind elderly in rural China: Prevalence and associated factors

Abstract: The prevalence of depressive symptoms is higher in left-behind elderly in rural areas than in the general elderly population. Psychological intervention is necessary for improving the mental health of elderly people living in rural areas of China. Geriatr Gerontol Int 2016; 16: 638-643.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 15 publications
(23 reference statements)
3
73
2
2
Order By: Relevance
“…The rate (57.4%) of DS of elderly caregivers (age ≥60 years) also was higher than that of other studies among the elderly in China (He et al., ; Xu et al., ). In rural China, grandparents take over the responsibility for parenting when both parents migrate to urban areas.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The rate (57.4%) of DS of elderly caregivers (age ≥60 years) also was higher than that of other studies among the elderly in China (He et al., ; Xu et al., ). In rural China, grandparents take over the responsibility for parenting when both parents migrate to urban areas.…”
Section: Discussioncontrasting
confidence: 55%
“…Mothers had a lower rate (37.5%) of depressive symptoms compared with fathers and grandparents, but it was still much higher than that of previous studies conducted among mothers with young children (Chang et al, 2014, Horwitz, Briggs-Gowan, Storfer-Isser, & Carter, 2007. The rate (57.4%) of DS of elderly caregivers (age ࣙ60 years) also was higher than that of other studies among the elderly in China (He et al, 2016;Xu et al, 2016). In rural China, grandparents take over the responsibility for parenting when both parents migrate to urban areas.…”
Section: Ds Of Caregivermentioning
confidence: 60%
“…In our study is shown that older women were more likely to suffer from depression than men. This finding is in accordance with the results of the previous studies in the field 2,28,29 . Quite contrary, Baiyewu et al found no differences between the opposite sexes 27 .…”
Section: Discussionsupporting
confidence: 94%
“…A study in China also showed that the overall prevalence of depression in the older adult was 36.9%, and reported that the prevalence of symptoms was higher in women 50.4% as compared to men 33.3%. In general, the prevalence of moderate to severe depression was 3.9% in their study [28]. The prevalence of mildmoderate depression and mild-severe depression was reported to be 27, and 12% in a study in Greek, respectively [29].…”
Section: Discussionmentioning
confidence: 81%